Coated Glass Substrates
A simplified coating structure with Al, Zn, and Sn oxynitride dielectric layers addresses the complexity and cost of existing glass substrates, maintaining optical and mechanical properties during heat treatment, thus reducing capital investment and enhancing manufacturing efficiency.
Patent Information
- Application Number
- JP2022527876
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-13
- Filing Date
- 2020-11-13
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-11-13
AI Technical Summary
Existing coated glass substrates require complex and expensive layer sequences for low emissivity and solar control, leading to increased capital investment and disruption in manufacturing, and fail to maintain optical properties and mechanical robustness during heat treatment.
A simplified coating structure with a lower antireflection layer, silver-based functional layer, barrier layer, and a dielectric layer comprising aluminum (Al), zinc (Zn), and tin (Sn) oxynitride, which maintains optical properties and mechanical robustness during heat treatment.
The solution provides coated glass substrates with high light transmission, low emissivity, and good solar control properties, while reducing the number of layers and capital investment, and ensuring stability and durability during heat treatment.
Smart Images

Figure 0007618669000005 
Figure 0007618669000001 
Figure 0007618669000002
Abstract
Description
[Technical field]
[0001] The present invention relates to coated glass substrates and methods for their manufacture. More particularly, the present invention relates to heat-treatable coated glass substrates with a reduced number of layers in the coating and further comprising a low-emissivity and / or solar control coating. [Background technology]
[0002] Glass coatings that provide low-emissivity (low-e) and / or solar control may be deposited by a physical vapor deposition process, such as, for example, sputtering. Glass coatings deposited by sputtering are typically produced by passing a glass substrate through one or more chambers that have a target bombarded with ions or atoms. The bombarded target ejects material, which coats the glass substrate. Sputtered low-e and solar control coating stacks are typically produced by, for example, "Substrate / base anti-reflective layer sequence / [silver (Ag) / anti-reflective layer sequence] n (each of the "n" antireflective layers does not necessarily have the same thickness or composition), An anti-reflective layer typically comprises one or more dielectric layers.
[0003] There is a continuing demand from the glass manufacturing industry for coated glass substrates capable of meeting the stringent performance requirements of automotive and architectural glazing, and as a result, ever more complex layer sequences (or stacks) are used to coat the glass substrates based on various dielectric materials. As a result, it is becoming more common in the glass manufacturing industry for "n" in the above sequences to be equal to 2, or even 3 or 4.
[0004] Previously, the deposition of multiple coating layers onto a glass substrate was addressed by installing expensive extensions to the coating line in the glass manufacturing plant to provide a sufficient number of chambers to deposit the various coating materials required in sufficient numbers, thicknesses and sequences.
[0005] This resulted in additional pump sections being installed in the extensions, making it possible to run multiple reactive deposition processes in sequence. However, this can only be achieved at great expense and often with major disruption, as the coating line typically needs to be shut down for long periods to complete the necessary engineering installations. Each additional chamber and pump section also requires the incorporation of accompanying power supplies, vacuum pumps, conveyor sections, services, instrumentation and control systems. Such modifications often lead to restructuring of downstream logistics and in some cases even new civil works or building extensions. As requirements for multiple metal layers and / or more complex stacks become increasingly common, these problems are set to increase.
[0006] Additionally, dielectric layers are often deposited by sputtering thicker and slower than metal layers such as silver, which further increases the number of chambers required as multiple chambers may be required to efficiently deposit a single dielectric layer.
[0007] It is also a requirement for architectural or automotive glazing to have a coated glass substrate that can be heat treated and therefore toughened to impart safety properties and / or bent to the required shape.
[0008] It is known that for thermal strengthening and / or bending (also known in the glass industry) of glass substrates, it is necessary to heat treat the glass substrate to a temperature close to or above the softening point of the glass, and then rapidly cool and / or bend the glass substrate using suitable bending means. Tempering or bending of standard float glass of soda-lime-silica type is usually achieved by heating the glass to a temperature of 580-690°C and maintaining the glass substrate in this temperature range for a few minutes before starting the actual strengthening and / or bending process.
[0009] "Heat treatment," "heat treated," and "heat treatable" in the following description and claims refer to thermal bending and / or strengthening processes (also known as tempering) and other thermal processes in which the coated glass substrate reaches a temperature in the range of, for example, 580-690°C for a period of several minutes, for example up to about 10 minutes. A coated glass substrate is considered heat treatable if it withstands the heat treatment without significant damage. Examples of significant damage to a glass substrate caused by heat treatment include, for example, increased haze (or cloudiness), pinholes or spots.
[0010] The use of coated glass substrates with coating layers comprising doped metal oxide layers is known. For example, US 2009 / 0197077 A1 describes a transparent glass substrate provided with a thin-film multilayer comprising a functional layer based on silver or a silver-containing metal alloy and two coatings composed of a number of dielectric layers, such that the silver functional layer is located between the two coatings. The functional layer is deposited on a wetting layer which is itself deposited directly on the underlying coating. The underlying coating comprises at least one dielectric layer based on nitrides and at least one amorphous smoothing layer made of a mixed oxide in the form of antimony-doped zinc stannate in contact with the immediately above wetting layer.
[0011] US Patent No. 6,541,133 discloses a layer stack for the surface coating of transparent substrates, comprising at least one metal oxide composite layer produced by reactive cathode sputtering, containing zinc oxide (Zn) and tin oxide (Sn). Based on the total amount of metals, this metal oxide composite layer may also contain 0.5 to 6.5% by weight of one or more of the elements Al, Ga, In, B, Y, La, Ge, Si, P, As, Sb, Bi, Ce, Ti, Zr, Nb and Ta.
[0012] US Patent No. 9,315,414 discloses a method for forming a low-emissivity (low-e) panel based on a transparent substrate. A metal oxide layer is formed on the transparent substrate. The metal oxide layer includes oxygen, a first element, a second element and a third element. The first element is tin or zinc. The second element is strontium and the third element is hafnium.
[0013] However, none of the above mentioned prior art documents provides a heat-treatable coated glass substrate having a layer sequence according to the invention that is capable of providing the desired optical properties, as well as the abrasion and scratch resistance requirements of the glass industry. Summary of the Invention
[0014] It is therefore an object of the present invention to provide an improved heat-treatable coated glass substrate, the optical properties of which do not change significantly or only change a small amount when heat-treated, for example, the color change of the coated glass substrate caused by heat treatment is preferably such that, if desired, a heat-treated coated glass sheet and a non-heat-treated coated glass substrate can be glazed adjacent to each other in use without noticeable color differences.
[0015] It is also an object of the present invention to provide a heat-treatable low-e and / or solar control coated glass substrate that is capable of withstanding normal environmental influences, for example during storage, transport and use, both before and after heat treatment. Furthermore, it is an object of the present invention to provide a heat-treatable low-e and / or solar control coated glass substrate that is capable of withstanding the mechanical and chemical conditions acting on the coated glass substrate during normal handling and processing without significant damage, as detailed below in connection with a series of tests.
[0016] The present invention further aims to provide heat-treatable coated glass substrates having high light transmittance, low emissivity (corresponding to low sheet resistance) and / or good solar control properties, i.e., the glass substrate has low solar energy transmittance combined with a sufficiently high light transmittance. A further object of the present invention is to provide such heat-treatable coated glass substrates with a reduced number of coating layers compared to existing substrates, thereby reducing the capital investment required to manufacture such coated substrates.
[0017] In summary, the present invention seeks to address the problems associated with the prior art processes and products detailed above, and seeks to provide economically efficient and commercially desirable coated glass substrates that meet the required optical properties of the glass industry, such as haze, light transmission, color, etc., and that are also robust enough to withstand thermal strengthening.
[0018] According to a first aspect of the present invention, there is provided a coated glass substrate, comprising, in order from the glass substrate: A lower anti-reflective layer; A silver-based functional layer; A barrier layer; A top anti-reflective layer; and Here, the upper anti-reflection layer is A coated glass substrate is provided that includes a dielectric layer of an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) having at least 5 atomic percent aluminum (Al).
[0019] In the coated glass substrate according to the first aspect of the invention, the dielectric layer may comprise an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) having at least 10 atomic percent aluminum. Alternatively, the dielectric layer may comprise an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) having at least 15 atomic percent aluminum, or the dielectric layer may comprise an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) having at least 22 atomic percent aluminum.
[0020] Also in relation to the first aspect of the invention, the dielectric layer preferably comprises an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) having up to 45 atomic percent aluminum. More preferably, the dielectric layer comprises an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) having up to 40 atomic percent aluminum. Alternatively, the dielectric layer may comprise an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) having up to 35 atomic percent aluminum.
[0021] Thus, in a preferred embodiment of the present invention, the dielectric layer preferably comprises an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) with aluminum ranging from 5 atomic percent aluminum to 45 atomic percent aluminum. Alternatively, the dielectric layer may comprise an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) with aluminum ranging from 5 atomic percent aluminum to 40 atomic percent aluminum. The dielectric layer may comprise an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) with aluminum ranging from 5 atomic percent aluminum to 35 atomic percent aluminum. In one embodiment of the present invention, the dielectric layer may comprise an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) with aluminum ranging from 10 atomic percent aluminum to 35 atomic percent aluminum. In an alternative embodiment of the present invention, the dielectric layer may comprise an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) with aluminum ranging from 20 atomic percent aluminum to 35 atomic percent aluminum. In further embodiments of the present invention, the dielectric layer may comprise an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) having aluminum ranging from 20 atomic percent aluminum to 30 atomic percent aluminum. In a preferred embodiment of the present invention, the dielectric layer may comprise an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) having aluminum ranging from 22 atomic percent aluminum to 28 atomic percent aluminum.
[0022] Preferably, the dielectric layer based on oxynitrides of aluminum (Al), zinc (Zn) and tin (Sn) comprises an atomic percentage of zinc of up to 30% and an atomic percentage of tin of up to 15%.
[0023] The dielectric layer based on oxynitrides of aluminum (Al), zinc (Zn) and tin (Sn) may preferably have a thickness of at least 5 nm. Alternatively, the dielectric layer based on oxynitrides of aluminum (Al), zinc (Zn) and tin (Sn) may preferably have a thickness of 10 to 50 nm. More preferably, the dielectric layer based on oxynitrides of aluminum (Al), zinc (Zn) and tin (Sn) may preferably have a thickness of 20 to 40 nm. Even more preferably, the dielectric layer based on oxynitrides of aluminum (Al), zinc (Zn) and tin (Sn) may preferably have a thickness of 30 to 40 nm. Most preferably, the dielectric layer based on oxynitrides of aluminum (Al), zinc (Zn) and tin (Sn) may preferably have a thickness of 32 to 36 nm. Such a thickness leads to an improvement in terms of mechanical robustness of the coated substrate. Said dielectric layer based on oxynitrides of aluminium (Al), zinc (Zn) and tin (Sn) may preferably be in direct contact with the layer based on an oxide of zinc (Zn) of the upper dielectric layer.
[0024] Dielectric layers based on oxynitrides of aluminum (Al), zinc (Zn) and tin (Sn) can preferably improve the stability of the coated glass substrate, i.e. improve protection during heat treatment, and preferably function as a diffusion barrier. In addition, dielectric layers based on oxynitrides of aluminum (Al), zinc (Zn) and tin (Sn) can preferably function as a protective layer, which provides improved mechanical and / or chemical robustness, such as scratch resistance.
[0025] In the present invention, the lower antireflection layer is preferably made of, in order from the glass substrate, a layer based on oxides of zinc (Zn) and tin (Sn) or oxides of tin (Sn), a layer based on an oxide of zinc (Zn); It may comprise:
[0026] The layer based on oxides of zinc (Zn) and tin (Sn) or oxides of tin (Sn) preferably has a thickness of 0.5 to 10 nm.
[0027] The lower antireflection layer may also preferably comprise one or more base layers based on silicon and / or aluminum (oxy)nitrides and / or alloys of silicon and / or aluminum. The one or more base layers based on silicon and / or aluminum (oxy)nitrides and / or alloys of silicon and / or aluminum are preferably arranged between the glass substrate and the layer based on oxides of zinc (Zn) and tin (Sn) present in the lower antireflection layer. Preferably, the base layer has a thickness of 20 to 40 nm.
[0028] In addition, the base layer may preferably be in direct contact with a layer based on oxides of zinc (Zn) and tin (Sn) or oxides of tin (Sn).
[0029] Therefore, in the context of the present invention, the lower anti-reflection layer is preferably formed from the glass substrate in the following order: a base layer based on (oxy)nitrides of silicon and / or aluminum and / or alloys of silicon and / or aluminum; a layer based on oxides of zinc (Zn) and tin (Sn) or oxides of tin (Sn), a separation layer based on metal oxides and / or (oxy)nitrides of silicon and / or aluminum and / or alloys of silicon and / or aluminum, a layer based on an oxide of zinc (Zn); Equipped with.
[0030] Alternatively, the bottom anti-reflective layer is preferably formed directly from the glass substrate in the following order: a base layer based on (oxy)nitrides of silicon and / or aluminum and / or alloys of silicon and / or aluminum; a layer based on oxides of zinc (Zn) and tin (Sn) or oxides of tin (Sn), a layer based on an oxide of zinc (Zn); It may comprise:
[0031] That is, the lower anti-reflective layer may preferably include three or four consecutive layers as described above. Whether the lower anti-reflective layer preferably includes three or four layers as described above depends on the number of silver-based functional layers present in the coating sequence.
[0032] When the coating sequence comprises only a single silver-based coating layer, the lower antireflective layer preferably consists of four layers in succession as described above, preferably including a separating layer, or when the coating sequence comprises two or more silver-based coating layers, the lower antireflective layer preferably consists of three layers in succession as described above, i.e. no separating layer is present.
[0033] The base layer based on silicon and / or aluminum (oxy)nitrides and / or alloys of silicon and / or aluminum of the lower antireflection layer may preferably have a thickness of at least 5 nm. More preferably, the base layer has a thickness of 5 to 60 nm. Even more preferably, the base layer has a thickness of, for example, 10 to 50 nm, 15 to 45 nm or 20 to 40 nm. Most preferably, the base layer of the lower antireflection layer has a thickness of 25 to 35 nm. One of the uses of the base layer in the coated glass substrate of the invention is to act as a glass-side diffusion barrier, i.e. the barrier layer seeks to prevent the migration of, for example, sodium ions into the coating layer.
[0034] The term "silicon (oxy)nitride" refers to silicon (Si) nitride (SiN x ) and silicon (Si) oxynitride (SiO x N y ), and the term "aluminum (oxy)nitride" includes aluminum (Al) nitride (AlN x ) and aluminum (Al) oxynitride (AlO x N y) are included. Silicon nitride (Si), silicon oxynitride (Si), aluminum nitride (Al) and aluminum oxynitride (Al) layers are substantially stoichiometric (e.g., silicon nitride = Si3N4, SiN x The value of x in (x=1.33) is preferred, but it can be sub-stoichiometric or even superstoichiometric, as long as the heat processability of the coating is not adversely affected thereby. One preferred composition of the silicon (oxy)nitride and / or aluminum (oxy)nitride based base layer of the lower antireflection layer is the substantially stoichiometric mixed nitride Si 90 Al 10 N x It is.
[0035] The silicon (oxy)nitride and / or aluminum (oxy)nitride layers can be reactively sputtered from silicon (Si) and / or aluminum (Al) based targets, respectively, in a sputtering atmosphere containing nitrogen and argon. The oxygen content of the silicon (oxy)nitride and / or aluminum (oxy)nitride based base layer can result from residual oxygen in the sputtering atmosphere or from a controlled content of added oxygen in said atmosphere. Generally, it is preferred if the oxygen content of the silicon (oxy)nitride and / or aluminum (oxy)nitride is significantly lower than its nitrogen content, i.e. the atomic ratio O / N in the layer is kept significantly below 1. Most preferred is the use of silicon nitride and / or aluminum nitride with negligible oxygen content for the base layer of the lower antireflection layer. This feature can be controlled by ensuring that the refractive index of the layer does not differ significantly from that of the oxygen-free Si nitride and / or aluminum nitride layer.
[0036] It is within the scope of the present invention to use mixed silicon (Si) and / or aluminum (Al) targets or otherwise add metals or semiconductors to the silicon (Si) and / or aluminum (Al) components of this layer, so long as the substantial barrier and protective properties of the base layer of the lower antireflective layer are not compromised. For example, aluminum (Al) and silicon (Si) targets can be mixed, and other mixed targets are not excluded. The additional components can typically be present in amounts of 10-15% by weight. Aluminum is typically present in mixed silicon targets in amounts of 10% by weight.
[0037] The zinc (Zn) and tin (Sn) oxide-based or tin (Sn) oxide-based layer of the lower antireflective layer preferably improves stability during heat treatment by providing a dense and thermally stable layer, and also contributes to reducing haze after heat treatment. The zinc (Zn) and tin (Sn) oxide-based or tin (Sn) oxide-based layer of the lower antireflective layer may preferably have a thickness of at least 0.5 nm. Preferably, the zinc (Zn) and tin (Sn) oxide-based or tin (Sn) oxide-based layer of the lower antireflective layer may have a thickness of 0.5 to 15 nm or 0.5 to 13 nm or 0.5 to 10 nm or 1 to 12 nm. In addition, the zinc (Zn) and tin (Sn) oxide-based or tin (Sn) oxide-based layer of the lower antireflective layer may have a thickness of 1 to 7 nm or 2 to 6 nm or 3 to 6 nm. Most preferably, the zinc (Zn) and tin (Sn) oxide-based or tin (Sn) oxide-based layer of the lower antireflection layer, together with the layer sequence with a single silver-based functional layer, may have a thickness of 3 to 5 nm for the coated glass substrate. Due to the optical interference conditions and the reduced heat treatability due to the resulting reduction in the thickness of the base layer required to maintain the optical interference boundary conditions of the antireflection functional layer, an upper thickness limit in the region of 8 nm is preferred.
[0038] In an alternative embodiment related to the first aspect of the invention, when the coated glass substrate comprises two or more silver-based functional layers, the zinc (Zn) and tin (Sn) oxide-based or tin oxide (Sn)-based layer of the lower antireflective layer preferably has a thickness of at least 12 nm. More preferably, the zinc (Zn) and tin (Sn) oxide-based or tin oxide-based layer of the lower antireflective layer has a thickness of 12 nm to 20 nm. Even more preferably, the zinc (Zn) and tin (Sn) oxide-based or tin oxide-based layer of the lower antireflective layer has a thickness of 12 nm to 16 nm. However, most preferably, the zinc (Zn) and tin (Sn) oxide-based or tin oxide-based layer of the lower antireflective layer has a thickness of 12 nm to 14 nm.
[0039] The zinc (Zn) and tin (Sn) oxide-based or tin (Sn) oxide-based layer of the lower antireflection layer is preferably arranged directly on a base layer based on a silicon (oxy)nitride and / or aluminium (oxy)nitride and / or an alloy base of silicon and / or aluminium.
[0040] The zinc (Zn) and tin (Sn) oxide-based or tin (Sn) oxide-based layer of the lower antireflection layer is made of zinc (Zn) and tin (Sn) oxide (abbreviation: ZnSnO x), the layer may preferably comprise 10-90 wt. % zinc (Zn) and 90-10 wt. % tin (Sn), more preferably about 40-60 wt. % zinc (Zn) and about 40-60 wt. % tin (Sn), even more preferably about 50 wt. % zinc (Zn) and tin (Sn), respectively, in weight percent of the total metal content of the layer. In some preferred embodiments, the zinc (Zn) and tin (Sn) oxide-based layer of the lower antireflective layer may comprise up to 18 wt. % tin (Sn), more preferably up to 15 wt. % tin (Sn), even more preferably up to 10 wt. % tin (Sn). The Zn and Sn oxide-based layer may also be deposited by reactive sputtering of a mixed ZnSn target, preferably in the presence of O2.
[0041] Preferably, the lower antireflective layer further comprises a separation between a layer based on an oxide of zinc (Zn) and tin (Sn) or a layer based on an oxide of tin (Sn) and a layer based on an oxide of zinc (Zn).
[0042] The separation layer preferably comprises a metal oxide and / or an (oxy)nitride of silicon and / or an (oxy)nitride of aluminium and / or an alloy of silicon and / or aluminium.
[0043] In addition, the separation layer may preferably have a thickness of at least 0.5 nm, or may preferably have a thickness of 0.5-6 nm, more preferably 0.5-5 nm, even more preferably 0.5-4 nm, and most preferably 0.5-3 nm. These preferred thicknesses allow for further improvement of haze during heat treatment. The separation layer preferably provides protection during the deposition process and during subsequent heat treatment. The separation layer is preferably either substantially fully oxidized immediately after deposition or oxidized to a substantially fully oxidized layer during the deposition of a subsequent oxide layer.
[0044] The separating layer may preferably comprise a metal oxide and / or a silicon and / or aluminium (oxy)nitride and / or an alloy of silicon and / or aluminium. When the separating layer is based on a metal oxide, said separating layer may preferably comprise a layer based on an oxide of Ti, Zn, NiCr, InSn, Zr, Al and / or Si. When the separating layer is preferably based on a metal oxide, it is, for example, a slightly substoichiometric titanium oxide, e.g. TiO 1.98 They can be deposited as substantially stoichiometric or slightly substoichiometric oxides using non-reactive sputtering from a Ti-based ceramic target, by reactive sputtering of a Ti-based target in the presence of O2, or by depositing a thin Ti-based layer which is then oxidized. In the context of the present invention, "substantially stoichiometric oxide" means an oxide that is at least 95% but up to 100% stoichiometric, while "slightly substoichiometric oxide" means an oxide that is at least 95% but less than 100% stoichiometric.
[0045] In addition to the metal oxides and / or (oxy)nitrides of silicon and / or aluminum on which it is based, and / or alloys of silicon and / or aluminum, the separation layer may further comprise one or more other chemical elements selected from at least one of the elements Ti, V, Mn, Co, Cu, Zn, Zr, Hf, Al, Nb, Ni, Cr, Mo, Ta, Si or alloys based on at least one of these materials, for example used as dopants or alloying agents. However, preferably, a separation layer based on metal oxides and / or (oxy)nitrides of silicon and / or aluminum does not comprise one or more other chemical elements.
[0046] In a preferred embodiment of the invention, the separating layer is based on a metal oxide, preferably comprising an oxide of zinc (Zn) and / or an oxide of titanium (Ti).
[0047] When the layer sequence of the coated glass comprises one silver-based functional layer, it is particularly preferred that the separating layer is based on an oxide of titanium.
[0048] When the layer sequence comprises two or more silver-based functional layers, the separation layer may be based on an oxide of titanium, but when the layer sequence or stack comprises two or more silver-based functional layers, it may also be preferred that the layer sequence does not comprise a separation layer in the lower antireflection layer.
[0049] Furthermore, when based on titanium oxide, the separation layer preferably has a thickness of 0.5 to 3 nm.
[0050] The zinc oxide (Zn) based layer of the lower antireflective layer mainly serves as a growth-promoting layer for the subsequently deposited silver-based functional layer. The zinc oxide (Zn) based layer is optionally mixed with a metal such as aluminum (Al) or tin (Sn) in an amount of up to about 10% by weight (% by weight based on the target metal content). The usual content of said metal such as aluminum (Al) or tin (Sn) is about 2% by weight, with aluminum (Al) being preferred in practice. Zinc oxide (ZnO) and mixed zinc oxide (Zn) have proven to be very effective as growth-promoting layers, thereby helping to achieve a low sheet resistance at a given thickness of the subsequently deposited silver-based functional layer. The zinc oxide (Zn) based layer of the lower antireflective layer is preferably reactively sputtered from a zinc (Zn) target in the presence of oxygen (O2). Alternatively, the zinc oxide (Zn) based layer of the lower antireflective layer can be deposited by sputtering, for example, a ceramic target based on ZnO:Al in an atmosphere containing only zero or a small amount of oxygen, i.e., generally not more than about 5% by volume. The layer of the lower antireflection layer based on an oxide of zinc (Zn) may preferably have a thickness of at least 2 nm. More preferably, the layer of the lower antireflection layer based on an oxide of zinc (Zn) may preferably have a thickness of 2 to 15 nm or 3 to 12 nm. Even more preferably, the layer of the lower antireflection layer based on an oxide of zinc (Zn) may preferably have a thickness of 4 to 10 nm. Most preferably, the layer of the lower antireflection layer based on an oxide of zinc (Zn) may have a thickness of 5 to 8 nm.
[0051] In addition, in the context of the present invention, it is preferred that the zinc oxide (Zn) based layer of the lower antireflection layer is in direct contact with the silver-based functional layer. As a result, in a preferred embodiment of the present invention, the layer sequence between the glass substrate and the silver-based functional layer can consist of three or four layers of the above-mentioned lower antireflection layer.
[0052] The silver-based functional layer preferably consists essentially of silver without additives, as is usual in the field of low emissivity and / or solar control coatings. However, within the scope of the present invention, the properties of the silver-based functional layer may be modified by adding doping agents, alloying additives, etc., or by adding very thin metal or metal compound layers, as long as the properties of the silver-based functional layer required to function as an IR-reflective layer with high light transmission and low light absorption are not substantially impaired thereby.
[0053] The thickness of each silver-based functional layer is governed by its technical objective. For typical low emissivity and / or solar control purposes, the preferred layer thickness for a single silver-based layer may preferably be 5-20 nm, more preferably 5-15 nm, even more preferably 5-13 nm or 8-12 nm, most preferably 9-11 nm. At such layer thicknesses, light transmission values of more than 86% after heat treatment and normal emissivity of less than 0.05 can be easily achieved according to the invention for a single silver coating. If better solar control properties are required, the thickness of the silver-based functional layer may be appropriately increased or several spaced apart functional layers may be provided, as further described below.
[0054] Although the present invention is directed to coated substrates having only one silver-based functional layer, it is within the scope of the present invention to apply the concept of the present invention to prepare low-emissivity and / or solar control coatings with two or more silver-based functional layers. When providing two or more silver-based functional layers, all silver-based functional layers are preferably separated by intervening dielectric layers, collectively referred to herein as "central anti-reflection layers", to form a Fabry-Perot interference filter. This allows the optical properties of the low-emissivity and / or solar control coating to be further optimized for the respective application.
[0055] Preferably, each silver-based functional layer is separated from the adjacent silver-based functional layer by an intervening central anti-reflective layer, which may comprise a combination of one or more of the following layers: layers based on silicon (oxy)nitrides and / or aluminum (oxy)nitrides, layers based on oxides of Zn and Sn and / or oxides of Sn, and layers based on metal oxides, such as oxides of Zn.
[0056] In some preferred embodiments, each silver-based functional layer is separated from an adjacent silver-based functional layer by an intervening central antireflective layer, each central antireflective layer being spaced from the silver-based functional layer closest to the glass substrate by: It comprises, in order, at least a layer based on a silicon (oxy)nitride and / or an aluminum (oxy)nitride, a layer based on oxides of Zn and Sn and / or an oxide of Sn, and a layer based on a metal oxide such as an oxide of Zn.
[0057] The coated glass substrate according to the first aspect of the invention preferably also comprises a barrier layer, which is preferably placed in direct contact with the silver-based functional layer.
[0058] The barrier layer is preferably NiCrO x or with a layer based on zinc oxide (Zn). Zinc (Zn) or NiCrO x The barrier layer based on an oxide of preferably has a thickness of at least 0.5 nm. More preferably, it is based on Zn or NiCrO x The barrier layer based on an oxide of Zn or NiCrO has a thickness of 0.5 to 10 nm. x The oxide-based barrier layer has a thickness of 1 to 10 nm.
[0059] However, the barrier layer is NiCrO x When the layer is based on the above, it preferably has a thickness of 0.5 to 5 nm or 1.0 to 5 nm.
[0060] It has been found that when the barrier layer comprises a layer of mixed metal oxide sputtered from a mixed metal oxide target, excellent protection of the silver-based functional layer during the deposition process and high optical stability during heat treatment can be achieved. When the barrier layer is based on an oxide of zinc (Zn), the oxide can be a mixed metal oxide such as ZnO:Al. Particularly good results are obtained when the layer based on ZnO:Al is sputtered from a conductive ZnO:Al target. The ZnO:Al can be deposited to be fully oxidized or slightly suboxidized.
[0061] In addition, when the barrier layer comprises a layer based on an oxide of zinc (Zn), the barrier can in fact comprise several zinc oxide layers, not only on a mixed metal oxide such as ZnO:Al, but also on an oxide of zinc (Zn) and tin (Sn). Thus, suitable barrier layers are ZnO:Al, ZnSnO x , ZnO:Al. Such a triple barrier arrangement may preferably have a total thickness of 3 to 12 nm.
[0062] A further triple barrier arrangement is preferably formed, in order from the silver-based functional layer, of ZnO:Al / TiO x / ZnO:Al, ZnO:Al / ZnSnO x / ZnO:Al, TiO x / ZnSnO x / ZnO:Al, TiO x / ZnO:Al / TiO x , TiOx / ZnSnO x / TiO x and ZnO:Al / ZnSnO x / TiO x The layer combination may be selected from the group consisting of:
[0063] At least the portion of the barrier layer that is in direct contact with the silver-based functional layer is preferably deposited using non-reactive sputtering of an oxidized target to avoid damaging the silver.
[0064] In addition, it has further been found that, as an alternative to a barrier layer based on an oxide of zinc (Zn), a suitable protection of the silver-based functional layer during the deposition process and a high optical stability during heat treatment can be achieved if the barrier layer also comprises a mixed metal oxide based on nickel (Ni) and chromium (Cr), such as a layer of substoichiometric NiCrOx. This is particularly true when the coated glass substrate comprises two or more silver-based functional layers, but when the coated glass substrate comprises a single silver-based functional layer, a layer of substoichiometric NiCrOx is also sufficient. x A layer of may also be used.
[0065] Thus, for a coated glass substrate comprising two or more silver-based functional layers, where each silver-based functional layer is separated from an adjacent silver-based functional layer by an intervening central antireflective layer, each central antireflective layer has at least one antireflective layer extending from the silver-based functional layer closest to the glass substrate to the adjacent silver-based functional layer. a layer based on a mixed metal oxide comprising nickel (Ni) and chromium; a layer based on a mixed metal oxide based on zinc and aluminum; - a layer based on silicon (oxy)nitride and / or aluminium (oxy)nitride, a layer based on oxides of Zn and Sn or a layer based on oxides of Sn, a layer based on a metal oxide, such as an oxide of Zn; It is preferable to have
[0066] Also in relation to the first aspect of the invention, the coated glass preferably comprises a top anti-reflective layer. The top anti-reflective layer preferably comprises: (i) a layer based on oxides of zinc (Zn) and tin (Sn) or based on oxides of tin (Sn), (ii) a layer based on an oxide of zinc (Zn); Equipped with.
[0067] The Zn and Sn oxides or Sn oxide-based layers in the top antireflection layer may preferably have a thickness of at least 0.5 nm, more preferably at least 0.5 nm or 1 nm, or even at least 1.5 nm, but preferably less than 5 nm, more preferably at most 4 nm, even more preferably less than 4 nm, most preferably at most 3 nm, in particular 2 nm. These preferred thicknesses allow for easier deposition and improved optical properties such as haze, while maintaining mechanical durability.
[0068] The layer based on an oxide of Zn in the upper antireflection layer may preferably have a thickness of at least 0.5 nm, more preferably at least 0.5 nm or 1 nm, or even at least 1.5 nm, but preferably less than 5 nm, more preferably 4 nm. These preferred thicknesses also allow for easier deposition and improved optical properties such as haze, while maintaining mechanical durability.
[0069] Preferably, the layer in the upper antireflection layer is based on substantially stoichiometric metal oxide.The use of the layer based on substantially stoichiometric metal oxide in the upper antireflection layer, rather than metal layer or stoichiometric layer of less than 95%, brings about the very high optical stability of the coating during heat treatment, and effectively helps to keep the optical modification during heat treatment small.In addition, the use of the layer based on substantially stoichiometric metal oxide brings about the advantage in terms of mechanical robustness.
[0070] In the context of the present invention, the term "non-reactive sputtering" includes sputtering an oxide target in a low-oxygen atmosphere (i.e., zero or up to 5% oxygen by volume) to provide a substantially stoichiometric oxide.
[0071] Also, in the context of the present invention, where a layer is said to be "based" on one or more particular materials, this means that the layer comprises predominantly one or more of those materials in an amount of at least 50 atomic %, unless otherwise specified.
[0072] The layer is ZnSnO x Based on the above, "ZnSnO x " means mixed oxides of Zn and Sn, as explained and defined elsewhere in the description.
[0073] To minimize light absorption in the coating and reduce the increase in light transmission during thermal treatment, all individual layers of the upper and lower antireflective layers are preferably deposited with substantially stoichiometric composition.
[0074] To further optimize the optical properties of the coated substrate, the top anti-reflection layer may comprise further partial layers of suitable materials generally known for dielectric layers of low-emissivity and / or solar control coatings, in particular selected from one or more of the oxides of Sn, Ti, Zn, Nb, Ce, Hf, Ta, Zr, Al and / or Si, and / or (oxy)nitrides of Si and / or Al or combinations thereof. However, when adding such further partial layers, it must be ensured that the heat processability as aimed at here is not thereby impaired.
[0075] It is understood that any further layer may contain additives, such as dopants, or reaction products of reactive sputtering gases that modify its properties and / or facilitate its manufacture. In the case of oxide-based layers, nitrogen may be added to the sputtering atmosphere, leading to the formation of oxynitrides rather than oxides, and in the case of nitride-based layers, oxygen may be added to the sputtering atmosphere, leading to the formation of oxynitrides rather than nitrides.
[0076] The dielectric layer comprising an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) can be the outermost layer on the coated glass substrate. Alternatively, the coated glass substrate can further comprise at least one additional layer, such that the dielectric layer of oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) is between the at least one additional layer and the glass substrate. Preferably, the at least one additional layer comprises either a layer based on oxides of zinc (Zn) and tin (Sn) or a layer based on oxides of tin (Sn), and / or a layer based on oxides of zirconium (Zr). Such additional layers can increase the durability of the coated substrate.
[0077] It is clear that the choice of material, structure and thickness of any layer in the sequence stack is important and that any changes thereto may adversely affect the coating performance. Thus, it is clear that when adding further layers to the existing layer sequence described above in connection with the present invention, the properties of the coating stack, such as high thermal stability, are not significantly compromised.
[0078] According to a second aspect of the present invention, (i) providing a glass substrate; (ii) providing a bottom antireflective layer; (iii) providing a silver-based functional layer; (iv) providing a barrier layer; (v) providing a top antireflective layer; There is provided a method for producing a coated glass substrate according to a first aspect of the invention comprising: (vi) providing a dielectric layer comprising an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn), wherein the dielectric layer comprises at least 5 atomic percent aluminum, and wherein any portion of the barrier layer in direct contact with the silver-based functional layer is deposited by sputtering in an atmosphere having less than 5 volume percent oxygen.
[0079] The invention is not limited to a specific manufacturing process of the coating. However, it is particularly preferred that at least one of the layers, and most preferably all layers, are applied by magnetron cathode sputtering, in which a metallic or semiconducting target is sputtered reactively or non-reactively in a suitable sputtering atmosphere, either in DC mode, pulse mode, medium wave mode or any other suitable mode. Depending on the material to be sputtered, planar or rotating tubular targets may be used.
[0080] Layers based on oxides of Zn, Ti, ZnSn, InSn, Zr, Al, Sn and / or Si and / or (oxy)nitrides of Si and / or Al can be deposited from non-reactive sputtering. The layers can be sputtered from ceramic targets.
[0081] Layers based on oxides of Zn, Ti, ZnSn, InSn, Zr, Al, Sn and / or Si and / or (oxy)nitrides of Si and / or Al can also be deposited by reactive sputtering: the layers can be sputtered from one or more metal targets.
[0082] The coating process is carried out by setting suitable coating conditions so that any oxygen (or nitrogen) deficiency in any oxide (or nitride) layer of the anti-reflective layer of the coating is kept low, thus achieving high stability of light transmittance and color of the coated glass substrate during heat treatment.
[0083] The light transmission values referred to herein generally refer to the light transmission T of 90% of the area without any coating. L The coated glass substrate is specified with reference to a standard float glass substrate having a thickness of 4 mm.
[0084] The color of the coated glass substrate according to the invention, although achromatic reflection and transmission color of the coated glass substrate is usually targeted, can be greatly modified by appropriate adaptation of the thicknesses of the individual layers according to the intended visual appearance of the product.
[0085] The thermal stability of the coated glass substrate according to the invention is reflected by the fact that the heat treated coated glass substrate does not show an unacceptable level of haze. If a significant increase in haze value (haze scan) is detected during heat treatment, it indicates that the coating is starting to be damaged. The mechanical durability of the coated glass substrate according to the invention is exemplified by its performance in an oil rub test.
[0086] According to a third aspect of the invention, there is provided a multiple glazing unit incorporating a coated glass substrate according to the first aspect of the invention or prepared by a method according to the second aspect of the invention. Additionally, the multiple glazing unit according to the third aspect of the invention may be a laminated glazing unit or an insulating glazing unit.
[0087] In addition, all features and priorities related to the coated glass substrate and layer sequence of the first aspect of the invention are also preferred with respect to the second and third aspects of the invention, including, for example, but not limited to, details of the bottom anti-reflective layer, top anti-reflective layer, silver-based functional layer, barrier layer and dielectric layer.
[0088] The invention will now be described in more detail by reference to the following non-limiting examples.
[0089] In relation to the examples, FIG. 1 shows the AlZnSnO x N y 1 is a graphical representation of haze scan and scratch load values versus atomic % of Al in [Brief description of the drawings]
[0090] [Figure 1] FIG. 1 is a graphical representation of haze scan and scratch load values versus atomic % of Al in AlZnSnOxNy for Experimental Examples 2-7.
[0091] A series of experiments was carried out to evaluate the effect of using a dielectric layer comprising oxynitrides of aluminum (Al), zinc (Zn) and tin (Sn) with at least 5 atomic percent aluminum deposited in a layer stack sequence on a float glass substrate. A series of experiments was carried out to evaluate the effect of using a dielectric layer comprising oxynitrides of aluminum (Al), zinc (Zn) and tin (Sn) with at least 5 atomic percent aluminum deposited in a layer stack sequence on a float glass substrate.
[0092] A series of coating layers (called a stack) was deposited on a float glass substrate. The coating layers included at least one silver-based coating layer. The series of layers is shown in Tables 1, 2, and 3.
[0093] In all examples, the coating layers were deposited onto 4 mm thick standard float glass substrates with 90% area light transmittance using single or dual magnetrons with MF-AC and / or DC magnetron (or pulsed DC) power supplies.
[0094] Zinc and tin oxide (ZnSnO x ) dielectric layers were reactively sputtered from a zinc-tin target (weight ratio Zn:Sn approx. 50:50) in an argon / oxygen (Ar / O2) sputtering atmosphere.
[0095] Titanium dioxide (TiO x The CrN 2 ) layer was deposited from a metallic titanium (Ti) target in an argon / oxygen (Ar / O 2 ) sputtering atmosphere.
[0096] The ZnO:Al growth-promoting top layer of the lower antireflective layer was sputtered from an Al-doped Zn target (aluminum (Al) content about 2 wt %) in an Ar / O 2 sputtering atmosphere with less than 5 vol % oxygen.
[0097] In all experimental examples, a functional layer consisting of substantially pure silver (Ag) was sputtered from a silver target in an Ar sputtering atmosphere without any added oxygen and with a residual oxygen partial pressure of less than 10-5 mbar. A barrier layer of Al-doped zinc oxide (ZnO:Al) on top of the silver-based functional layer was sputtered from a conductive ZnO:Al target in an Ar / O2 sputtering atmosphere with less than 5% oxygen by volume. x : Sputtered from an Al target.
[0098] Mixed silicon aluminum nitride (Si 90 Al 10 N x ) layer was sputtered in an argon / nitrogen (Ar / N2) atmosphere containing only residual oxygen by mixing Si 90 Al 10 It was reactively sputtered from the target.
[0099] A layer of AlN was reactively sputtered from an Al target in an argon / nitrogen (Ar / N2) sputtering atmosphere containing only residual oxygen.
[0100] The mixed aluminum, zinc, tin, oxynitride layers were deposited on two aluminum targets and a conductive ceramic mixed zinc tin oxide (ZnSnO) in an Ar / O2 / N2 atmosphere. x )) targets were used for co-sputtering.
[0101] Tables 1, 2 and 3 provide details of the coating layer sequence, with the geometric thickness of each layer given in nanometers (nm) in brackets. For comparative coated glass substrate examples and coated glass substrate examples according to the invention, each example is: Metal content of the outermost layer, haze scan, oil friction test value, slip angle test value, scratch load test value, T L%-Light transmittance (%) of glass substrate before heat treatment, ΔT L - change in light transmittance (%) upon heat treatment, Rs AD - sheet resistance before heat treatment, Rs HT - sheet resistance after heat treatment, ΔRs (Ω / square) - change in heat resistance, TΔE* - a measure of the change in transmitted color upon heat treatment.
[0102] For each example, the layers were deposited on the glass plate in the order shown, starting with the top layer in each row.
[0103] [Table 1]
[0104] [Table 2-1] [Table 2-2]
[0105] [Table 3]
[0106] The methodology used to collect the data in Tables 1, 2 and 3 is presented below.
[0107] Oil Rub Test - The oil rub test serves to simulate the effect of cutting oils used in cutting glass substrates on the mechanical robustness of the coating. Coated glass substrates that do not withstand the oil rub test are difficult to process and unsuitable for most practical applications. Coated samples, as defined in Tables 1, 2 and 3, are rubbed using a felt pad of 1.2x1.2cm area immersed in microscopic oil with a refractive index of 1.52 (1.515-1.517). The sample is subjected to 500 cycles with a load of 1,000g and a speed of 37 cycles per minute. The oil rubbed samples are then rated on an integrity scale from 0 (perfect, no damage) to 9 (part of the coating stack has been completely removed) using an internal rating system. A score of 6 or less is preferred.
[0108] Heat Treatability Test - Immediately after the deposition of all coatings for each experimental example, the coating stack parameters (haze scan, sheet resistance (Rs), light transmittance (TL), etc.) and the color coordinates of the coated glass substrate were measured. The samples were then heat treated in the 650°C region for 5 minutes. After that, the haze scan values, sheet resistance (Rs), light transmittance (TL), etc. were measured. L ), the color coordinates were measured again, and the change in light transmittance (ΔT L ) and the change in transmitted color upon heat treatment (TΔE*) were calculated. The measurement results are also shown in Tables 1, 2, and 3 above.
[0109] Light transmittance (ΔT L The values stated in percentage (%) for the change in thermal expansion coefficient (SSC) are derived for each experimental example from measurements according to EN 140, the details of which are incorporated herein by reference.
[0110] Sheet Resistance / Change in Sheet Resistance - Sheet resistance measurements were made using a NAGYSRM-12 for Comparative Examples 1 and 8 and Experimental Examples 2-7 and 9-12. This device utilizes an inductor to generate eddy currents in a 100 mm x 100 mm coated sample. This generates a measurable magnetic field, the magnitude of which is related to the resistivity of the sample. Using this method, the sheet resistance may be calculated. This equipment was used to measure the sheet resistance of samples before and after heat treatment at 650°C for 5 minutes.
[0111] Color Properties - The color properties of each experimental example in Tables 1, 2 and 3 are based on established CIE LAB L * ,a * ,b * The change in transmitted color upon heat treatment, TΔE, was measured and reported using coordinates (e.g., as described in paragraphs
[0030] and
[0031] of WO 2004 / 063111, which is incorporated herein by reference). * =((Δa * ) 2 +(Δb * ) 2 +(ΔL * ) 2 ) 1 / 2 , where ΔL * , Δa * , and Δb * is the color value L of each coated glass substrate before and after heat treatment * , a * , b * A ΔE of less than 3 (e.g., 2 or 2.5) * The values are favorable for layer sequences with one silver-based functional layer, which exhibit low and almost no noticeable color changes caused by the heat treatment. For layer sequences with two or more silver-based functional layers, the lower TΔE * The TΔE value provides an indication of the stability of the sequence. * The lower the value, the better the results and appearance of the coated glass substrate.
[0112] Haze Scan - A haze scoring system was applied to each of the experimental examples described in Tables 1, 2, and 3. The quality assessment system described below was also used to more clearly distinguish the visual quality of the coatings under bright light conditions, a property that is not fully reflected in the standard haze value measured according to ASTM D1003-61.
[0113] The evaluation system considers the more macroscopic effects of visible defects in the coating, which cause local color changes if the coating is damaged or incomplete (haze scans in Tables 1, 2 and 3). The evaluation analyzes the light levels of images of heat-treated samples taken using fixed lighting conditions and geometry.
[0114] To generate the image used to calculate the Haze Scan value, the sample is placed inside a black box 30 cm from the camera lens. The sample is illuminated using a standard 1200 lumen light, which has a brightness of 2400-2800 lux when measured at the sample position. The sample is then photographed using a constant aperture size and exposure length. The greyscale of each pixel in the resulting image is then recorded. A value of 0 represents black and 255 represents white. A statistical analysis of these values is performed to make an overall assessment of the haze of the sample, referred to here as the Haze Scan value. The lower the recorded Haze Scan value, the better the result.
[0115] Slip Angle Test - Slip angle measurements provide an indication of the coefficient of friction of the outermost layer of a coating. To complete the test, the sample is placed on a steel flatbed and a block with two felt pads attached to the bottom is placed on top of the sample so that the felt pads are in contact with the sample. The angle of the flatbed is tilted until the block slides off the sample, generating a slip angle.
[0116] Scratch Load Test - The scratch load test is a measurement of the ability of a coating to resist scratching. The test is performed using a sclerometer with a tungsten carbide tip. The tip is dragged across the surface at several adjacent locations. This process is repeated with increasing loads applied to the sclerometer until three significant scratches are observed. Significant scratches are defined as continuous scratches or removal of large amounts of material from the coating. Higher loads indicate greater resistance to scratching.
[0117] (Summary of results) Comparative Example 1 has an AlN upper anti-reflection layer disposed around the first silver-based functional layer. x and ZnSnO x The stack has a dielectric layer of 1000 nm. Comparative Example 1 gives good results in haze scan values and mechanical robustness tests. However, Comparative Example 1 has AlN in the top anti-reflection layer. x layer and ZnSnO x Thus, Comparative Example 1 does not address the objective of the present invention, namely, to reduce the number of coating layers in a stack sequence and thereby reduce the capital investment required to manufacture such a coating sequence.
[0118] Similarly, Comparative Example 8 has ZnSnO at the top of the stack sequence. x The dielectric layer is AlN x Comparative Example 8 shows poor performance in terms of haze scan values, which is due to the absence of a ZnSnO x The single layer of AlN x and ZnSnO x This indicates that the bilayer is not a suitable monolayer replacement for the
[0119] Experimental Examples 2 to 7 and 9 to 12 of the present invention are the same as those of Comparative Example 1, AlN x and ZnSnO x AlZnSnO to replace the dielectric layer x N yThe amounts of aluminum (Al), zinc (Zn) and tin (Sn) are different in each of Experimental Examples 2 to 7 and 9 to 12.
[0120] All examples according to the invention exhibited acceptable optical properties with transmission values of over 79%, a change in transmission value of less than 3.5 after heat treatment, and a change in color value of less than 3.5 after heat treatment. In addition, all examples exhibited acceptable electrical properties with sheet resistance values of less than 7 Ω / sq and a change in sheet resistance value of less than 2.5 after heat treatment.
[0121] In terms of haze scan results, Examples 2-7 and 9-12 according to the invention all provided acceptable values of about 200 or less. However, as shown in Figure 1, certain improvements in the haze scan were observed in Examples 3 and 4 (compared to the values obtained in Comparative Example 1 in Table 1), and Example 2 also provided an acceptable haze scan value. Example 9 in Table 3 also provided an acceptable haze scan value.
[0122] Figure 1 also shows that Example 2 exhibited particularly good mechanical durability with a value of 1.0 for the scratch load test, thus providing a good compromise when durability is desired over reduced haze.
[0123] Therefore, from the above results, it can be seen that the coated glass substrate of the present invention has a top anti-reflection layer of AlZnSnO x N y It has been found that a single dielectric layer of (wherein the amount of aluminum in the layer comprises at least 5 atomic percent) provides good thermal processability and mechanical durability.
[0124] The coated glass substrates of the present invention also exhibit low levels of visible damage according to tests simulating use, processing and handling conditions. Additionally, the coated glass substrates exhibit high light transmission and low emissivity and / or good solar control properties, and the optical properties remain stable even after heat treatment.
[0125] The coated glass substrates according to the invention may be suitable for use in architectural glazing such as buildings, including insulating glazing units and facades. Alternatively, the coated glass substrates according to the invention may be suitable for use in vehicle glazing such as passenger cars, mass transit vehicles and buses, freight vehicles and marine or aircraft glazing including windscreens, backlights, rooflights, sidelights and quarterlights.
Claims
1. A coated glass substrate, comprising, in order from the glass substrate: A lower anti-reflective layer; A silver-based functional layer; A barrier layer; A top anti-reflective layer; and Here, the upper anti-reflection layer is a dielectric layer of aluminum (Al), zinc (Zn) and tin (Sn) oxynitride having at least 5 atomic percent aluminum (Al); Coated glass substrate.
2. 10. The coated glass substrate of claim 1, wherein the dielectric layer of aluminum (Al), zinc (Zn) and tin (Sn) oxynitride comprises up to 45 atomic percent aluminum.
3. 3. The coated glass substrate of claim 1, wherein the dielectric layer of oxynitrides of aluminum (Al), zinc (Zn) and tin (Sn) has a thickness of 10 to 50 nm.
4. 4. The coated glass substrate of claim 1, wherein the dielectric layer of oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) comprises an atomic percent of zinc up to 30% and an atomic percent of tin up to 15%.
5. The coated glass substrate according to any one of claims 1 to 4, wherein the barrier layer is in direct contact with the silver-based functional layer.
6. The barrier layer has a thickness of 1 to 10 nm and is made of NiCrO x 6. The coated glass substrate according to claim 1 , further comprising a layer based on an oxide of zinc (Zn).
7. The lower antireflection layer is formed by, in this order from the glass substrate, a layer based on oxides of zinc (Zn) and tin (Sn) or oxides of tin (Sn); a layer based on an oxide of zinc (Zn); The coated glass substrate of any one of claims 1 to 6, comprising:
8. 8. The coated glass substrate of claim 7, wherein the layer based on oxides of zinc (Zn) and tin (Sn) or oxides of tin (Sn) has a thickness of 0.5 to 15 nm or 12 to 20 nm.
9. 9. The coated glass substrate according to claim 7 or 8, wherein the lower anti-reflective layer further comprises a separation layer located between the layer based on an oxide of zinc (Zn) and tin (Sn) or an oxide of tin (Sn) and the layer based on an oxide of zinc (Zn).
10. 10. The coated glass substrate of claim 9, wherein the separation layer has a thickness of 0.5 to 6 nm.
11. The separation layer is Metal oxides and / or (Oxy)nitrides of silicon and / or aluminum and / or an alloy of silicon and / or aluminum; 11. The coated glass substrate of claim 9 or 10, comprising:
12. 12. The coated glass substrate of claim 11, wherein when the separation layer is based on a metal oxide, the metal oxide comprises an oxide of zinc (Zn) and / or an oxide of titanium (Ti).
13. 13. The coated glass substrate according to claim 11 or 12, wherein the separation layer further comprises one or more other chemical elements selected from at least one of the elements Ti, V, Mn, Co, Cu, Zn, Zr, Hf, Al, Nb, Ni, Cr, Mo, Ta, Si or an alloy based on at least one of these materials.
14. The lower anti-reflection layer further comprises a base layer located between the glass substrate and the layer based on oxides of zinc (Zn) and tin (Sn) or oxides of tin (Sn), wherein the base layer comprises: (Oxy)nitrides of silicon and / or aluminum and / or comprising an alloy of silicon and / or aluminum; wherein the base layer has a thickness of 20 to 40 nm.
14. A coated glass substrate according to any one of claims 7 to 13.
15. 15. The coated glass substrate of claim 14, wherein the base layer is in direct contact with the layer based on oxides of zinc (Zn) and tin (Sn) or oxides of tin (Sn).
16. 16. Coated glass substrate according to any one of claims 7 to 15, wherein the zinc oxide (Zn) based layer in the lower antireflective layer has a thickness of 2 to 15 nm.
17. 17. The coated glass substrate according to claim 7, wherein a layer based on zinc oxide (Zn) in the lower antireflection layer is in direct contact with a silver-based functional layer.
18. Coated glass substrate according to any one of claims 1 to 17, wherein the silver-based functional layer has a thickness of 5 to 20 nm.
19. The upper anti-reflective layer is (i) a layer based on oxides of zinc (Zn) and tin (Sn) or oxides of tin (Sn), (ii) a layer based on an oxide of zinc (Zn); The coated glass substrate of any one of claims 1 to 18, comprising:
20. A coated glass substrate as described in claim 19, wherein the thickness of the layer based on zinc (Zn) and tin (Sn) oxide or tin (Sn) oxide in the upper antireflective layer is in the range of 1 to 10 nm.
21. A coated glass substrate as described in claim 19 or 20, wherein the thickness of the zinc (Zn) oxide-based layer in the upper antireflective layer is in the range of 1 to 10 nm.
22. 22. The coated glass substrate of any one of claims 1 to 21, wherein the substrate comprises two or more silver-based functional layers, where each silver-based functional layer is separated from an adjacent silver-based functional layer by an intervening central anti-reflective layer.
23. 23. The coated glass substrate according to any one of claims 1 to 22, further comprising at least one additional layer in the top antireflective layer, wherein the at least one additional layer is arranged above or below a dielectric layer of an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn) having at least 5 atomic percent aluminum (Al), and wherein the at least one additional layer comprises an oxide of zinc (Zn) and tin (Sn) or a layer based on an oxide of tin (Sn) and / or a layer based on an oxide of zirconium (Zr).
24. (i) providing a glass substrate; (ii) providing a bottom antireflective layer; (iii) providing a silver-based functional layer; (iv) providing a barrier layer; (v) providing a top antireflective layer; (vi) providing a dielectric layer comprising an oxynitride of aluminum (Al), zinc (Zn) and tin (Sn), wherein the dielectric layer comprises at least 5 atomic percent aluminum, and wherein any portion of the barrier layer in direct contact with the silver-based functional layer is deposited by sputtering in an atmosphere containing less than 5 volume percent oxygen.
25. 24. A multiple glazing unit incorporating the coated glass substrate of any one of claims 1 to 23.
Citation Information
Patent Citations
Heat-treatable coated glass panes
JP2014512329A
Low-E Panels With Ternary Metal Oxide Dielectric Layer And Method For Forming The Same
US20130164561A1
Systems, methods, and apparatus for production coatings of low-emissivity glass including a ternary alloy
US20140268316A1
Coated glass pane
WO2019186131A1